Mode of Delivery and Obstetric Complications in the Setting of Prior Uterine Surgery - Bogardus, Margaret H.; Friedman, Alexander M.; Arora, Chetna; D'Alton, Mary E.; Wen, Timothy (American Journal of Perinatology, 2023)
Objective This study aimed to evaluate cesarean rates and risk for obstetric complications among deliveries with a history of prior uterine surgery.Study Design This serial cross-sectional study analyzed deliveries with and without prior uterine surgery in the 2016–2019 Nationwide Inpatient Sample. Unadjusted and adjusted logistic regression models were performed to assess risk of nontransfusion severe maternal morbidity (SMM) and other obstetric complications based on the presence or absence of prior uterine surgery with unadjusted and adjusted odds ratios (aORs) with 95% confidence intervals (CIs) as measures of association. Adjusted models accounted for demographic, hospital, and delivery factors. Demographics and clinical factors among deliveries with and without a prior history of uterine surgery diagnosis were compared with the chi-square test with p < 0.05 considered statistically significant.Results Of 14.7 million delivery hospitalization identified, 6,910 (4.7 per 10,000) had a history of uterine surgery and 111,710 (0.76%) experienced SMM. Women with prior uterine surgery were more likely to be older, to be of unknown race or ethnicity, and to have private insurance (p < 0.01 for all). Eighty-five percent of deliveries with prior uterine surgery were performed by cesarean compared with 32% of deliveries without prior uterine surgery (p < 0.01). In adjusted analysis, compared with patients without prior uterine surgery, patients with prior uterine surgery were not at increased risk for SMM (aOR 1.23, 95% CI 0.73–2.07). Evaluating obstetric complications, patients with prior uterine surgery had a decreased risk of postpartum hemorrhage (aOR 0.64, 95% CI 0.43–0.96) and an increased risk of peripartum hysterectomy (aOR 4.12, 95% CI 1.75–9.67), and no difference in other obstetric complications assessed.Conclusion These findings suggest that current clinical practice results in similar delivery risks among patients with compared with without prior uterine surgery.Key Points
Keywords: maternal morbidity; obstetric complications; uterine scar; uterine surgery